Kangaroo mother care prior to clinical stabilisation: Implementation barriers and facilitators reported by caregivers and healthcare providers in Uganda. - Victor S Tumukunde; Joseph Katongole; Stella Namukwaya; Melissa M Medvedev; Moffat Nyirenda; Cally J Tann; Janet Seeley; Joy E Lawn (Public Library of Science (PLoS), 2024)
Kangaroo mother care (KMC) is an evidence-based method to improve newborn survival. However, scale-up even for stable newborns has been slow, with reported barriers to implementation. We examined facilitators and barriers to initiating KMC before stabilisation amongst neonates recruited to the OMWaNA study in Uganda. The OMWaNA study was a randomised controlled trial that examined the mortality effect of KMC prior to stabilisation amongst newborns weighing ≤2000 grams. At the four trial hospitals, we conducted focus group discussions (FGD) separately with caregivers and healthcare providers, in-depth interviews (IDI) with caregivers and key informant interviews (KII) with hospital administrators and healthcare providers. The World Health Organisation (WHO) Health Systems Building Blocks were used to guide thematic analysis. Eight FGDs (4 caregivers, 4 healthcare providers), 41 caregiver IDIs (26 mothers, 8 grandmothers, 7 fathers), and 23 KIIs were conducted. Key themes based on the building blocks were; family and community support/ involvement, health workforce, medical supplies and commodities, infrastructure and design, financing, and health facility leadership. We found that the presence of a family member in the hospital, adequate provision of healthcare workers knowledgeable in supporting KMC prior to stability, and adequate space for KMC beds where neonatal care is being delivered, can enable implementation of KMC before stability. Implementation barriers included fear of inadvertently causing harm to the newborn, inadequate space to practice KMC in the neonatal unit, and a limited number of trained healthcare workers coupled with insufficient medical supplies.